In situ observation of compression damage in a 3D needled-punched carbon fiber-silicon carbide ceramic matrix composite. (15th February 2019) - Wan, Fan; Liu, Rongjun; Wang, Yanfei; Cao, Yingbin; Zhang, Changrui; Marrow, Thomas James
Abstract: Damage development has been observed in situ within a 3-dimensional needle-punched carbon fiber reinforced carbon and silicon carbide (C/C-SiC) ceramic composite, as compressive loads were applied longitudinally, transversely and obliquely to its anisotropic structure. Laboratory X-ray computed tomographs were analyzed using digital volume correlation to measure the local strains. Cracks exist within the microstructure before the application of load, due to thermal strains, and their propagation is affected by the heterogeneous microstructure and the direction of loading. The punched carbon fiber needles are observed to restrict the propagation of damage.